KEPENTINGAN JEPANG BEKERJASAMA DENGAN TIONGKOK DALAM ABENOMICS TAHUN 2013 - ", Rehesa; Tjarsono, Idjang (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research will examine to found what is Japanese interests to cooperate with Tiongkok in an economic policy that created by Japanese Prime Minister Shinzo Abe is the call with Abenomics.this research an aim to xplain economic policy of Shinzo Abe. This research was conducted by using the method of research literature where the data and information obtained from sources that are relevant to this research problem.This research uses liberalism perspective to analyze the interests of Japan and Japan's efforts to improve its alliance with Tiongkok. The theory used in this research is the economic theory of Keynes pointed out that called Keynesian liberalization. The studies discussed in this research is the study of international political economy.The results of this study illustrate Japan needs Tiongkok as a means to prop up the economy after the deflation that occurred in 2011 were caused by the tsunami disaster that damages parts of Japan. As for Japan's economic policy with regard to choosing Japan chose Tiongkok because Tiongkok is one country that has the largest economy and influential in the world.Japan also wants to improve its alliance with Tiongkok worsened, due to historical facto and disputes. Japanese efforts made to improve is to cooperate in the field of investment, exports and imports and reduce territorial dispute occurs through negotiationsKeywords: Abenomics, improvement of Japan-Tiongkok relations, cooperation